BUSINESS ANALYTICS: BUSINESS ENABLER FOR SMALL AND MEDIUM ENTERPRISES - Vijay Garg, Suhas Ambekar, Manoj Hudnurkar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose: Business analytics has emerged as a business facilitator in every aspect of the business. Policymakers can see key-performance-indicators, integrated data sources, and predict trends by implementing BA in the organizations. Innovation and Flexibility in Small and medium size businesses and enterprises are vital for the Indian economy in generating employment and contributing to economic development. The sole objective of this research is to identify the specific areas of business analytics for SMEs that will lead these organizations a better understanding of the business world. Proposed-Design/Methodology/Approach: After a short review of the literature, Feedback will be taken from SMEs through questionnaires to understand which area is important and where they need to be focused on to be successful. In this regard, Business research- Survey techniques will be used. Exploratory data analysis will be used for gaining insight from the data.